Digital Subtraction Angiogram (DSA) is Superior to Duplex Ultrasound (USD) in Diagnosis of Extracranial Carotid Stenosis - A Comparative Study (Journal of Medicine, 2011)
This retrospective crossectional observational study was conducted in the department of Neurology, DMCH, Dhaka from December 2008 to December 2009. This study included a total of 40 patients, out of all, 35 suffered from nondisabling ischaemic stroke, other 5 had TIAs. Patients with ≥50% extracranial carotid stenosis on Duplex Ultrasound were then selected for DSA. DSA was done on these vessels and stenosis was measured using NASCET criteria. Results of USD and DSA were compared to determine the sensitivity, specificity and accuracy of Duplex Ultrasound (USD). ROC graph of RICA and LICA showed that most left and upper point of the curve lies at the level of 70% stenosis. At ≥70% stenosis of RICA and LICA the Sensitivity, Specificity and Accuracy were 91.2%, 50%, 85% and 86.83%, 50%, 85% respectively. This level of diagnostic efficiency of USD is less than that of DSA of carotid arteries. Study revealed that USD underestimates or overestimates degree of carotid stenosis, and DSA is safe and effective in determining stenosis. So before taking any decision to intervene in the form of Carotid endarterectomy or carotid artery stenting, it would be wise to do Digital Subtraction Angiogram of carotid vessels. Key word: Digital Subtraction Angiogram; Duplex Ultrasound; carotid vessels. DOI: 10.3329/jom.v12i1.6926J Medicine 2011; 12 : 12-16